2018
DOI: 10.1183/13993003.02120-2017
|View full text |Cite
|
Sign up to set email alerts
|

CSF1R inhibition prevents radiation pulmonary fibrosis by depletion of interstitial macrophages

Abstract: Radiation-induced lung fibrosis (RIF) is a delayed side-effect of chest radiotherapy, frequently associated with macrophage infiltration.We aimed to characterise the role of pulmonary macrophages in RIF using human lung biopsies from patients receiving radiotherapy for thorax malignancies and a RIF model developed in C57BL/6 mice after 16-Gy thorax irradiation.High numbers of macrophages (both interstitial and alveolar) were detected in clinical and preclinical RIF. In the preclinical model, upregulation of T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
135
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(140 citation statements)
references
References 30 publications
2
135
0
3
Order By: Relevance
“…9 Accordingly, in our recent study, we showed that lung alveolar macrophages (AM) that are newly recruited to the lungs after the depletion induced by thoracic IR exposure are activated, as they present an increase in both the expression of Arg1, CD206 and Icam1. 8 This result suggests that these AMs, which have not been directly exposed to IR, are activated by the existing signals rather than directly by IR. However, several in vitro studies underscore the direct effect of IR in macrophage activation.…”
Section: Macrophage Response To Radiotherapymentioning
confidence: 97%
See 4 more Smart Citations
“…9 Accordingly, in our recent study, we showed that lung alveolar macrophages (AM) that are newly recruited to the lungs after the depletion induced by thoracic IR exposure are activated, as they present an increase in both the expression of Arg1, CD206 and Icam1. 8 This result suggests that these AMs, which have not been directly exposed to IR, are activated by the existing signals rather than directly by IR. However, several in vitro studies underscore the direct effect of IR in macrophage activation.…”
Section: Macrophage Response To Radiotherapymentioning
confidence: 97%
“…12 Several studies have described the secretion of inflammatory cytokines after IR in vivo . 4,8 Inflammatory cytokines produced in vivo by irradiated cells could act as bystander factors to induce the abscopal effect. Interestingly, macrophages have been proposed as an important source of bystander signals in vivo .…”
Section: Immediate Immunological Consequences Of Irmentioning
confidence: 99%
See 3 more Smart Citations